1995
DOI: 10.1136/gut.36.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Retained common bile duct stones after endoscopic sphincterotomy: temporary and longterm treatment with biliary stenting.

Abstract: [446][447][448][449]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
1
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 14 publications
2
35
1
8
Order By: Relevance
“…Stones were extracted after a median of 63 d, and the repeated procedures achieved complete duct clearance in 25 (89%) of the patients. Similar results have also been reported by Maxton et al [21] and Jain et al [22] . The most common complications we observed were cholangitis and pancreatitis (14.3% and 4.8%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…Stones were extracted after a median of 63 d, and the repeated procedures achieved complete duct clearance in 25 (89%) of the patients. Similar results have also been reported by Maxton et al [21] and Jain et al [22] . The most common complications we observed were cholangitis and pancreatitis (14.3% and 4.8%, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…In the majority of retained CBDS after ERCP, plastic stents are the most employed temporizing measure (11)(12)(13)(14)(15)(16)(17)(18)(19). This solution is good in the first months after the index ERCP, but in the long term, there can be major complications such as cholangitis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested that permanent biliary stenting may be a definitive therapy for endoscopically unextractable common duct stones in selected elderly patients who are poor surgical candidates. When biliary symptoms do recur, they can usually be treated conservatively with antibiotics, a prosthesis change, or both [2,13] . To the best of our knowledge, our case report represents the oldest in situ plastic biliary endoprosthesis ever reported in the literature.…”
Section: Discussionmentioning
confidence: 99%